Acute disseminated encephalitis in an adult patient addicted to heroin. Neuropathological, neuroradiological and clinical features - Sobstyl, Michał; Rzehak, Anna; Szczechowski, Dawid; Acewicz, Albert; Mackiewicz, Ewelina; Kurkowska-Jastrzębska, Iwona (Folia Neuropathologica, 2022)
Acute disseminated encephalomyelitis (ADEM) is an immune demyelinating central nervous system (CNS) disorder, characterized by monophasic new onset neurological symptoms including encephalopathy, combined with neuroradiological evidence of multifocal demyelination. ADEM is extremely rarely diagnosed and is much more common in children and adolescents than in adults. The aim of this study is to present an extremely rare case of ADEM in a heroin-addicted patient with a very difficult diagnostic course. The results of the magnetic resonance imaging (MRI) examination in this patient were inconclusive. Fungal abscesses or inflammatory lesions of an unclear nature were suspected especially in a patient with impaired immunodeficiency. In view of the constantly deteriorating condition of the patient with disturbed consciousness and the unclear aetiology, the lack of effective treatment, a decision was made to perform a bilateral stereotactic biopsy and aspiration of brain abnormalities in order to obtain a neuropathological specimen and begin with the causal treatment. Neuropathological examination revealed the presence of Creutzfeldt-Peters cells characteristic of ADEM. Treatment with methylprednisolone significantly improved the patient’s general and neurological condition. To our knowledge, the above case is the first in the world literature in which ADEM has been confirmed by bilateral stereotaxic aspiration for the treatment of symptoms of increased intracranial pressure as a lifesaving procedure. Neuropathological confirmation allowed for the implementation of appropriate treatment, which resulted in complete recovery. Moreover, this case is interesting because ADEM was diagnosed in a patient addicted to heroin, where opportunistic inflammation of a fungal aetiology was considered in the first place.